Optimization of protease production and sequence analysis of the purified enzyme from the cold adapted yeast Rhodotorula mucilaginosa CBMAI 1528 - Lario, Luciana Daniela; Pillaca Pullo, Omar Santiago; Durães Sette, Lara; Converti, Attilio; Casati, Paula; Spampinato, Claudia Patricia; Pessoa, Adalberto (Biotechnology Reports)
Enzymes from cold-adapted microorganisms are of high interest to industries due to their high activity at low and mild temperatures, which makes them suitable for their use in several processes that either require a supply of exogenous energy or involve the use of heat labile products. In this work, the protease production by the strain Rhodotorula mucilaginosa CBMAI 1528, previously isolated from the Antarctic continent, was optimized, and the purified enzyme analyzed. It was found that protease production was dependent on culture medium composition and growth temperature, being 20 °C and a culture medium containing both glucose and casein peptone (20 and 10 g/L, respectively) the optimal growing conditions in batch as well as in bioreactor. Moreover, mass spectrometry analysis revealed that the enzyme under study has a 100 % sequence identity with the deduced amino acid sequence of a putative aspartic protease from Rhodotorula sp. JG-1b (protein ID: KWU42276.1). This result was confirmed by the decrease of 95 % proteolytic activity by pepstatin A, a specific inhibitor of aspartic proteases. We propose that the enzyme reported here could be Rodothorulapepsin, a protein characterized in 1972 that did not have an associated sequence to date and has been classified as an orphan enzyme. Fil: Lario, Luciana Daniela. Pontificia Universidad Católica Argentina "Santa María de los Buenos Aires". Facultad de Química e Ingeniería del Rosario. Departamento de Investigación Institucional; Argentina. Universidade de Sao Paulo; Brasil. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Rosario. Centro de Estudios Fotosintéticos y Bioquímicos. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Centro de Estudios Fotosintéticos y Bioquímicos; Argentina Fil: Pillaca Pullo, Omar Santiago. Universidade de Sao Paulo; Brasil Fil: Durães Sette, Lara. Universidade Federal de Sao Paulo; Brasil Fil: Converti, Attilio. Università degli Studi di ...